Development of Species-specific Cichla species eDNA Primers for Rapid Alien Invasive Species (AIS) Monitoring - Nurul Fizatul Nabilah Osman; Adibah Abu Bakar; Syazwan Saidin; Ramizah Abdul Rahman; Intan Faraha Abd Ghani; Amirrudin A; Siti Azizah M. N. (Genetikawan Muda Indonesia, 2022)
Peacock bass or the cichlids are known locally as top predator fishes which are invasive in Malaysia freshwater system. Detection probabilities for these fishes are typically low, especially using the conventional capture-survey method due to the fish’s behaviour of hiding beneath the water’s surface. Hence, environmental DNA (eDNA) monitoring is a relatively new non-invasive and rapid approach that can be used to assess the distribution of these invasive fishes. Here, we report the strategy i) to develop small fragment (280- 400bp) specific-specific primers for three selected invasive Cichla species namely, C. kelberi, C. ocellaris, and C. monoculus based on mitochondrial DNA (mtDNA) COI gene sequences, ii) how high quality of DNA and e-DNA should be extracted and iii) how to validate primers for specificity, (iv) developed and tested a new quantitative PCR (qPCR) assay to detect the presence of C. kelberi, and C. ocellaris, environmental DNA (eDNA) in water samples. Current research showed that the cytochrome oxidase I (COI) gene can be used to developed species- specific primers for selected species. However, several primer-designed parameters need to be adjusted to improve the specificity of primers. These were discussed in detail with future recommendations for the researcher’s references. Moreover, we found the isolation of e-DNA needs to be done within 22 days of capture to prevent false-negative results. This data can be easily applied in any fish genomic-based lab with the low-cost setting as only AGE (Agarose Gel Electrophoresis) analysis was needed for validation procedures. Overall, e-DNA analysis with species- specific primers represents new monitoring tool in detection of Aquatic Invasive Species (AIS) for management and conservation purpose.